Fostering spirituality in the workplace a leader's guide to sustainability - Berry, Priscilla. (2013 digital library., 2013)
This book explores historical data, analyzes current events from the world stage, and delivers a worldview that challenges some existing paradigms in business. As we are living business history, the book draws from the epic economic, environmental, and cultural shifts in our collective consciousness. The impact of these deep and rapid changes on companies, employees, and the global economy cannot be underestimated and future world leaders must be prepared to lead in a manner that is socially responsible, ethical, and profitable. A corporation with a business model that polarizes or operates solely in the interest of its shareholders is unsustainable. Current benchmarks are unrealistic tools for businesses to rely upon as measures of future success. The mindset of profitability at any cost is causing us to grapple with a historically unprecedented world crisis, which threatens civilization, as we know it. A widespread erosion of ethics and responsible behavior in the business world has resulted from a failure of society and institutions of higher education to instill and teach moral principles.